Differential malondialdehyde (MDA) detection in plasma samples of patients with major depressive disorder (MDD): A potential biomarker. Issue 5 (May 2022) - Alvarez-Mon, Miguel A; Ortega, Miguel A; García-Montero, Cielo; Fraile-Martinez, Oscar; Lahera, Guillermo; Monserrat, Jorge; Gomez-Lahoz, Ana M; Molero, Patricio; Gutierrez-Rojas, Luis; Rodriguez-Jimenez, Roberto; Quintero, Javier; Alvarez-Mon, Melchor
Objective: To measure plasma levels of malondialdehyde (MDA), a marker of oxidative stress (OS), in patients with major depressive disorder (MDD) compared with healthy control (HC) subjects in order to determine if it is a possible biomarker of depression. Methods: This prospective cross-sectional study enrolled patients with MDD and HC subjects. The plasma levels of MDA were measured using a commercially-available colorimetric assay. Results: A total of 30 patients with MDD and 20 HC subjects with similar sex, age and body mass index distribution were enrolled in the study. Patients with MDD had significantly higher plasma levels of MDA than the HC subjects. Receiver operating characteristic curve analysis for plasma MDA levels in patients with MDD demonstrated an area under the curve of 0.9767. Conclusion: The findings of this current study provide further evidence of the role pathophysiological relevance of OS and MDA in MDD. This study provides the basis for the use of MDA as a biomarker for MDD.